Conjoined Twins and Multiple Pregnancy in Żuławy. A Contribution to Research on the History of Tocology - Kubus, Radosław; Naujocks, Wolfgang (Vade Nobiscum, tom XXII/2021: Studia z wieków dawnych, 2021)
Conjoined twins and multiple pregnancies are a topic that has not yet been elaborated. This text is only a small contribution, where on the basis of record books, reference books and the press, attempts are made to find cases of unusual birth. Certainly the data cited in the text are incomplete and need to be supplemented with further sources. The case of the birth of five children in the village of Lubieszewo, recorded in the record books for 1780, seems quite unique. Is this the first case of quintuplets in Poland to date? Without more detailed research on it, we will not know the answer to this question.